2021
DOI: 10.4103/jfmpc.jfmpc_2133_20
|View full text |Cite
|
Sign up to set email alerts
|

To study the awareness of osteoporosis in postmenopausal Indian women in a Northeast part of India

Abstract: Aim and Objective: Our study's objective is to determine the level of awareness in postmenopausal women in Guwahati, Northeast part of India, using the Osteoporosis Health Belief Scale (OHBS). Settings and Design: Osteoporosis is the most common silent health problem in postmenopausal Indian women. An awareness level among this subset of women needs to study. The present study is based on a self-explanatory questionnaire. Methods: We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…Complications associated with osteoporosis, particularly hip fractures, result in a mortality rate that is 4 times higher in the global adult population [ 132 ]. Despite its preponderance in the elderly, osteoporosis has shown to impact individuals of various age groups, but postmenopausal women are at high risk [ 134 , 135 ] due to a decrease in estrogen production which results in increased oxidative stress and osteoclast-induced bone resorption [ 136 ]. Studies have shown that children born to parents with a history of osteoporosis and fractures are more prone to the development of osteoporosis [ 137 ].…”
Section: Biological Activities Of Lycopenementioning
confidence: 99%
“…Complications associated with osteoporosis, particularly hip fractures, result in a mortality rate that is 4 times higher in the global adult population [ 132 ]. Despite its preponderance in the elderly, osteoporosis has shown to impact individuals of various age groups, but postmenopausal women are at high risk [ 134 , 135 ] due to a decrease in estrogen production which results in increased oxidative stress and osteoclast-induced bone resorption [ 136 ]. Studies have shown that children born to parents with a history of osteoporosis and fractures are more prone to the development of osteoporosis [ 137 ].…”
Section: Biological Activities Of Lycopenementioning
confidence: 99%